The Relationship of Belief, Experience, Knowledge, and Attitudes Toward Safety Behavior of Construction Workers at University X Ponorogo - Sisca Mayang Phuspa; Edwina Rudyarti (Indonesian Journal for Health Sciences, 2017)
Indonesia is a country with a record of accidents is quite high, where 38% of them are fallen from a height that is a work accident in the field of construction. The cause of high numbers is the implementation and supervision of OHS, as well as behavior of industrial society in particular and society in general that has not been optimal. Safety behavior is a safe working behavior of potential hazards. The factors that make up safety behavior are work experience, belief, knowledge, and attitude.The purpose of this research is to know the correlation between knowledge and attitudes toward safety behavior is carried out on the worker of lecturer residential development project of University X Ponorogo from June to August 2017. This research is a descriptive research with quantitative approach. Based on the time this research is a cross sectional study. The sample of this study amounted to 50 people with the technique of determining the total sampling.The results showed that there was a significant correlation between work experience with knowledge in construction worker of University X. As well as the belief in the fate of the worker with the knowledge. There is a significant relationship between work experience and worker attitude. As well as a significant relationship between the belief in the fate of the workers and the safety attitude to the construction worker of University X. However, there is no significant correlation between knowledge and safety attitude with safety behavior in construction worker of University X, because there is no enabling factor in the form of worker support facility to carry out safety behavior in their workplace.